Management of the ventilation in intraoperative tracheobronchial injury with manual occlusion of the rent—An unusual case report - Sofia Jaswal; Harsimran S. Walia; Lalita G. Mitra; Sahil Mittal (Saudi Journal of Anaesthesia)
Intraoperative tracheobronchial injury is one of the most serious complications of any thoracic surgery. Its management is really challenging both for the surgeons as well as for the anesthesiologists. We present a rare case of intraoperative tracheobronchial injury during esophagectomy and the management of the ventilation by intermittent manual occlusion of the rent as a rescue method. The left-sided bronchus got injured near the carina, while the patient was on one-lung ventilation in a lateral position and the left lung was being ventilated with a left-sided double-lumen tube (DLT). Surgeons decided to repair it in a lateral position and required the right lung to be deflated for surgical access. The endobronchial part of the tube was taken out in the trachea, and the patient was intermittently ventilated by occlusion of tracheal rent by the surgeon as a rescue measure. Intermittent apnea and ventilation were conducted, and the repair of tracheal rent was conducted in the apnea period. A negligible air leak was present after the repair. Manual occlusion of the rent can help restore ventilation in an emergency situation when other options are technically difficult.